Coordinated down-regulation of the antigen processing machinery in the gills of amoebic gill disease-affected Atlantic salmon ( Salmo salar L.) - Young, ND; Cooper, GA; Nowak, BF; Koop, BF; Morrison, RN (Permagon-Elseviers Science Ltd, 2008)
Several important cultured marine fish are highly susceptible to an ectoparasitic condition known as amoebic gill disease (AGD). In AGD-affected fish, modulation of IL-1, p53 and p53-regulated transcripts is restricted to the (multi)focal AGD-associated gill lesions. To determine whether this lesion-restricted modulation of transcripts occurs on a transcriptome-wide scale and to identify mechanisms that underpin the susceptibility of fish to AGD, we compared the transcriptome of AGD lesions with "normal" tissue from AGD-affected and healthy individuals. Global gene expression profiling using a 16 K salmonid microarray, revealed a total of 176 significantly regulated annotated features and of those, the modulation of 99 (56%) was lesion-restricted. Annotated transcripts were classified according to functional gene ontology. Within the immune response category, transcripts were almost universally down-regulated. In AGD-affected tissue, significant, coordinated down-regulation of the major histocompatibility complex class I (MHC I) pathway-related genes occurred during the later stages of infection and appeared to be mediated by down-regulation of interferon-regulatory factor (IRF)-1, independent of interferon-, interferon- and IRF-2 expression. Within this micro-environment, suppression of the MHC I and possibly the MHC II pathways may inhibit the development of acquired immunity and could explain the unusually high susceptibility of Atlantic salmon to AGD. 2008 Elsevier Ltd. All rights reserved.